(untitled) (Research, Society and Development, 2024)
Breast cancer is one of the leading causes of death among women in Brazil. Its treatment includes surgery, chemotherapy, hormone therapy, and radiotherapy, depending on the stage of the disease and the characteristics of the tumor. Radiotherapy is essential to eliminate residual cancer cells and reduce recurrences, which can have the “rebound effect,” where the cancer returns after an apparent remission due to the resistance of some cells to the treatment. Additionally, it can cause “tissue pull-back,” a retraction of irradiated tissues leading to fibrosis and aesthetic changes, negatively impacting the patient’s quality of life. Advancements such as intensity-modulated radiotherapy (imrt) have been developed to minimize these effects, but clinical monitoring and rehabilitation, such as physiotherapy, are essential to reduce discomfort and improve prognosis. Early screening, recommended for women aged 50 to 69, is crucial for earlier diagnoses, increasing the chances of cure. This study aims to provide a literature review on the impact of the rebound effect and how it affects the quality of life of breast cancer patients who have undergone radiotherapy. The research followed a qualitative approach, using the SciELO, PubMed, and Lilacs databases for data collection. Despite the side effects, radiotherapy is an important treatment in the fight against breast cancer. Technological innovations have reduced negative impacts, and the benefits outweigh the disadvantages, if the decision is personalized for each patient.